Exploration of different strategies of nanoencapsulation of bioactive compounds and their ensuing approaches - Sailee Chowdhury; Koyel Kar; Rana Mazumder (SpringerOpen, 2024)
Abstract Background Nanotechnology has gained rapid popularity in many fields, such as food science. The labile bioactive is enclosed in a shield that protects it from harmful environmental factors. It also allows for targeted delivery to specific areas. Bioactive compounds in foods are slowly degraded or can change due to external or internal factors such as oxidation. Innovative technologies and novel edible packaging materials can be used to reduce bioavailability. One promising technology for overcoming the problems above is encapsulation. The main body of the abstract Nanostructure systems enhances a number of properties, including resistance to degradation and improvements of physicochemical functions like solubility, stability, and bioavailability, among others as the nanosize increases surface area and, consequently, activity. A recently emerged nanoencapsulation technologies, including electro spraying, nano-fluidics, complex coacervation, electrospinning, polymerization, etc. have been briefly discussed. Different bioactive molecules can be nano encapsulated by absorbing, incorporating, chemically interacting, or dispersing substances into nanocarriers. There have also been other characterization techniques and different physico chemical parameters investigated to evaluate the characteristics of encapsulated bioactives. The current article highlights numerous bioactive substances utilized for nanoencapsulation using cutting-edge methods. Short conclusion This review examines how different encapsulating bioactive materials can improve encapsulating films or coatings. The advent of nanotechnology has opened up a wide range of possibilities for the development, design, and formulation of innovative pharmaceuticals. The food and pharmaceutical industry can focus its attention on products that have added value through the various enhancements offered by nanoencapsulation.